Lower cytokine secretion ex vivo by natural killer T cells in HIV-infected individuals is associated with higher CD161 expression - Snyder-Cappione, Jennifer E; Loo, Christopher P; Carvalho, Karina I; Kuylenstierna, Carlotta; Deeks, Steven G; Hecht, Frederick M; Rosenberg, Michael G; Sandberg, Johan K; Kallas, Esper G; Nixon, Douglas F (AIDS (London), 2009)
Natural killer T (NKT) cells are efficiently targeted by HIV and severely reduced in numbers in the circulation of infected individuals. The functional capacity of the remaining NKT cells in HIV-infected individuals is poorly characterized. This study measured NKT cell cytokine production directly ex vivo and compared these responses with both the disease status and NKT subset distribution of individual patients. NKT cell frequencies, subsets, and ex-vivo effector functions were measured in the peripheral blood mononuclear cells of HIV-infected patients and healthy controls by flow cytometry. We measured cytokines from NKT cells after stimulation with either alpha-galactosyl ceramide-loaded CD1d dimers (DimerX-alphaGalCer) or phorbol myristate acetate and ionomycin. The frequencies of NKT cells secreting interferon-gamma and tumor necrosis factor-alpha were significantly lower in HIV-infected patients than healthy controls after DimerX-alphaGalCer treatment, but responses were similar after treatment with phorbol myristate acetate and ionomycin. The magnitude of the interferon-gamma response to DimerX-alphaGalCer correlated inversely with the number of years of infection. Both interferon-gamma and tumor necrosis factor-alpha production in response to DimerX-alphaGalCer correlated inversely with CD161 expression. The ex-vivo Th1 responses of circulating NKT cells to CD1d-glycolipid complexes are impaired in HIV-infected patients. NKT cell functions may be progressively lost over time in HIV infection, and CD161 is implicated in the regulation of NKT cell responsiveness.